The Inner and the Outer Foreign Territory—~A Qualitative Study Measuring Ambiguity Tolerance Within Young Muslims Living in Germany - Lena Barth; Paul Kaiser; Gonca Tuncel-Langbehn; Barbara Ruettner; Lutz Goetzmann (Journal of International Migration and Integration, 2022)
Against the backdrop of globalisation on the one hand and nationalisation on the other, the question of tolerance of ambiguity, i.e. of tolerating cultural ambiguity and vagueness, is of particular importance. This qualitative study investigates what tolerance of ambiguity means in a group of 50 young Turkish Muslims living in Germany. A high tolerance of ambiguity is mentioned much more frequently in the interviews than a low tolerance of ambiguity with tendencies towards (religious) radicalisation. Appreciation of different cultures and lifestyles and a certain resilience to discrimination go hand in hand with a high tolerance of ambiguity. However, it is also possible that despite high tolerance of ambiguity, the corresponding attitudes remain ambivalent. A lack of support, difficult interpersonal conflicts (especially in one's own family), and a turn to religion occur together with expressions of low ambiguity tolerance. The casuistic representations deepen the impression that high ambiguity tolerance is favoured in triadically structured families functioning as a collective, whereas early traumatic experiences and emotional distance in crises promote low ambiguity tolerance, especially in adolescence. The results underline the importance of high tolerance of ambiguity on the part of both the host country and the migrants.
Keywords: 300; Integration; Ambiguity; Identity; Exclusion; Radicalisation